1992
DOI: 10.1002/bip.360320111
|View full text |Cite
|
Sign up to set email alerts
|

The interactions of neuropeptides with membrane model systems: A case study

Abstract: The interactions between the positively charged neuropeptides substance P (SP), bradykinin (BK), and zwitterionic Met-enkephalin (ME) neuropeptides, and negatively charged SDS and zwitterionic lysophosphatidylcholine (LPC) membrane model systems, have been investigated using one- and two-dimensional nmr experiments. Proton longitudinal relaxation studies were used to characterize these interactions as intrinsic or extrinsic. An extrinsic interaction are similar to those observed for extrinsic membrane proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
58
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 30 publications
7
58
0
Order By: Relevance
“…Two-dimensional NMR and molecular modeling investigations indicated that (Ala 8,13,18 )magainin 2 amide bound to DPC micelles adopts a ␣-helical secondary structure involving residues 2-16. The four C-terminal residues converge to a lose ␤-turn structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional NMR and molecular modeling investigations indicated that (Ala 8,13,18 )magainin 2 amide bound to DPC micelles adopts a ␣-helical secondary structure involving residues 2-16. The four C-terminal residues converge to a lose ␤-turn structure.…”
mentioning
confidence: 99%
“…
Abstract: The role played by noncovalent interactions in inducing a stable secondary structure onto the sodium dodecyl sulfate (SDS) and dodecylphosphocholine (DPC) micelle-bound conformations of (Ala 8,13,18 )magainin 2 amide and the DPC micelle bound conformation of magainin 1 were determined. Two-dimensional NMR and molecular modeling investigations indicated that (Ala 8,13,18 )magainin 2 amide bound to DPC micelles adopts a ␣-helical secondary structure involving residues 2-16.
…”
mentioning
confidence: 99%
“…Such a high degree of flexibility suggests that binding to the receptor implies the selection of a particular structure from among the number of slowly or rapidly interconverting ones in solution. As a matter of fact, enhancement of the b-turn-forming potential of bradykinin was observed in the presence of SDS micelles [16,24±27], apolar organic solvents [14,18,20,27] or aqueous phospholipids [13,22,26]; as a consequence of all these findings, bradykinin is currently believed to adopt a C-terminal b turn upon complexation with the receptor [28].In the present study, NMR data were collected for bradykinin in dimethylsulfoxide containing 1% water in the presence of calcium, in order to ascertain whether the conformational equilibria and structural heterogeneity are affected by a divalent metal ion that may act as a mediator in the process of conformational selection. The water/dimethylsulfoxide solvent was chosen because most biochemical functions occur away from bulk water but may involve active molecules that retain some water of hydration.…”
mentioning
confidence: 99%
“…Temperature coefficients were calculated from the TOCSY experiments at three different temperatures (288, 298, and 308 K) to investigate the intramolecular hydrogen bondings in the peptides. 19 NMR spectroscopy can give useful information about the interaction between the peptides and micelles. NOESY experiments for the sample in non-deuterated SDS micelles was executed at 298 K with mixing times of 250 and 600 ms. All NMR spectra were processed off-line using the FELIX software package on SGI (Molecular Simulations Inc., San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%